Assessing the needs of the labor market of Qom province for the specialization of graduates of technical and vocational fields - maliheh asghariajiri; hamid jafarian (Institute of Management fekrenoandish, 2021)
Extended AbstractAbstractThe present study was conducted to investigate the needs of the labor market for the specialization of students in technical-vocational branches of Qom province. This research is a survey in terms of practical purpose. The statistical population included all teachers in Qom province and the sample according to Cochran's formula was 259 people, and sampling method was the stratified quota. Data were collected by a researcher-made questionnaire and a checklist of disciplines in the technical-professional branch (40 disciplines) and the vocational branch (161 disciplines). Content validity was evaluated positively by the relevant professors, and reliability was calculated to be 0.78 with Cronbach's alpha. Kolmogorov-Smirnov test, one-sample t-test, and Friedman test were used to analyze the data. Mechanical equipment (with an average rank of 15/31), carpet handicrafts (with an average rank of 14.74); and in its field of expertise, troubleshooting computer systems, production and development of Internet sites, electric machines and computer game programming in the branch of expertise are market priorities in the work market of Qom province. In this study, new cases for educational management in the field of technical-vocational branches and skills in Qom province were introduced, which ultimately provides a good platform for employment growth and reducing unemployment among high school students. It is suggested that educational administrators include the identified priorities in their plans and base their educational activities on the results of scientific research, including the present study, in order to make the provided training effective.IntroductionIn order to accelerate their movement towards social and economic development, industrialized and developing countries seek to better and more economically exploit their important source of production, namely manpower (Genmaoui, 1991). The importance of technical-vocational education and its impact on economic development is not hidden from anyone. Today, technical-vocational education leaders, with great responsibility and wisdom, must take advantage of the potential opportunities that the new era brings along, by providing flexible leadership for their institutions (binNasir, 2021). There is a lot of evidence that increasing the level of skills by increasing investment in vocational training has enhanced the economic potential of countries (Abdollahi, 2016). Any inconsistency between the needs of the community and the skills of the graduates can be prevented by conducting a needs assessment for the vocational education curriculum (Rosina et. al, 2021). With regard to the relationship of the technical-vocational training impact on the job-creating skills (Abdullah et. al, 2021), Technical-professional training is one of the main methods of training specialized personnel. In this regard, the more the managers have a clear knowledge and understanding of their vision and direction, the more they can clearly define organizational goals and strategies for employees (Eyni, 2020). The progress of many countries has been achieved by relying on increasing the skills of human resources; however, based on existing research findings, it seems that in our country, the graduates of these trainings are not in line with the intended goals (Abbaszadeh et. al, 2018. (In order to improve the quality of technical and vocational education curricula, it is necessary to tailor the curricula to the professional needs of businesses and the link between employers and planners (Shafi, 2021). In fact, having a perspective, as well as defined goals and missions for achieving the determined goals is the introduction of getting acceptable results from training (Hadavand, 2020). Although in the field of vocational education implementation, the influence of determining factors related to resources and stakeholders is very vital (Caves et al., 2021), it seems that some levels of education are not organized in technical schools (Sangita, 2021). Paying attention to creating a connection between technical education and the labor market and trying to measure the climate needs in the distribution of technical disciplines will increase the efficiency of the professional technical field and is one of its needs. According to the Supreme Leader, the economic progress is not possible without work-affair enhancement and look at work (Statement in the meeting between teachers and workers, 1378/2/19). Considering that the lack of connection between the field of education and the labor market causes the waste of national capital, efforts to create information and communication bridges is essential to link industry and the job market to in-school training. In fact, short-term and medium-term goal setting in the education of the provinces based on the results of field research in the field of labor market and industry needs, paves the way for development, so the question can be asked: what are the labor market needs of Qom with regard to the skills of the graduates of this field?Theoretical frameworkA review of theoretical foundations and already-done research shows the importance of technical-vocational training in developed countries; for example, vocational training in Germany is often presented as a dual system, i.e. teaching and learning is done in two environments: One in the workplace such as factories, workshops, service offices, and the other in part-time technical-vocational schools, and whoever learns skills in a dual style is both a workplace intern and a student at school (Alavi Ilkhchi and Khosravi Babadi, 2014). Findings of Jalilian et.al (2017) showed that there is no correspondence between the existing performance of technical-vocational education and the desired situation (identified needs andpriorities of education) in Khorramshahr city. Research results demonstrate the importance of needs assessment in the branches of technical-vocational to be adapted to the labor market.MethodologyThe present study was applied in terms of purpose; and descriptive and survey in terms of data collection method. The statistical population of the study consisted of all students working in education colleges in Qom province in the academic year 2020-2021, which according to the organization of Education were 796 people. In this research, the quota targeted stratified sampling method was used in which each technical-vocational conservatory was involved in sampling according to its number and proportion. The sample size was determined through Cochran's formula of 259 people. Data were collected by means of library, field, questionnaire methods and evaluation checklists. Thus, by studying in the field of research, the main axes in two areas of external factors (recruiting the graduates in the labor market, tendency to employ graduates, matching market needs with the learning of the graduates) and internal factors (launching new disciplines equipment, course content, management style, teaching method) were identified and researcher-made questionnaire questions were designed based on these areas.Discussion and ResultsPrioritization of labor market needs of Qom province in the field of technical-vocational fields according to the significance of Friedman test related to the field of automotive mechanics with an average rank of 15.65 in the first priority, the field of mechanical installations with an average rank of 15.31 in the second priority, and the field of handicrafts (carpet) with an average rank of 14.74 was in the third priority of the needs of the labor market of Qom province. The field of photography with an average rank of 11.16 has the lowest needs of the labor market of Qom province. The field of troubleshooting computer systems with an average rank of 25.55 is the first rank and the most need of the labor market of Qom province in the field of its specialized fields. Also, the field of shielding gas welding with an average rank of 21.14 is the forty-sixth rank and has the lowest needs of the labor market of Qom province.ConclusionThe purpose of this study was to investigate the needs of the labor market in relation to the expertise of students in technical-vocational branches of Qom province.